Protective Effect of Colostrum Therapy in Premature Infants Weighing Less Than 1500g at the INMP 2018-2021: Efecto protector de calostroterapia en prematuros menores de 1500g en el INMP 2018-2021 - Dávila-Aliaga, Carmen Rosa (2024)
Background: Prematurity is a serious public health problem, due to its high morbidity and mortality, with 15 million premature births and one million deaths annually worldwide. The main causes of neonatal mortality in premature infants are necrotizing enterocolitis and late sepsis. In Peru, the percentage of premature births increased from 6.4% in 2020 to 7.5% in 2023, with an average of 30,000 premature newborns annually. In 2023, 70% of neonatal deaths corresponded to premature babies. The National Maternal Perinatal Institute reported high rates of neonatal mortality, especially in premature babies weighing less than 1500 grams. It is worth mentioning that of all neonatal deaths by 2023, 70% corresponded to premature babies and 46.5% to those less than 1500g. Objective: Determine the protective effect of colostrotherapy in premature newborns with birth weight less than 1500g in the INMP during the period 2018-2021. Methods: Longitudinal analytical observational and retrospective cohort study. The bivariate analysis was carried out, where the presence of the association between the variables and the administration of colostrotherapy was evidenced. In the multivariate analysis, 3 study models were proposed (model 1: necrotizing enterocolitis, model 2: requirement for mechanical ventilation and model 3: mortality), and Poisson-type multiple logistic regression was used, indicating the adjusted relative risk and its respective 95% confidence intervals. Results: In the multivariate analysis, the 1st model showed that colostrotherapy (adjusted RR: 0.304, 95% CI: 0.099-0.93) acts as a protective factor against necrotizing enterocolitis. In the 2nd model, colostrotherapy showed no association with the requirement for mechanical ventilation. And finally, in the 3rd model it was shown that colostrotherapy (RR: 0.494, 95% CI: 0.32-0.76) acts as a protective effect with respect to mortality. Conclusions: The administration of oropharyngeal colostrum is a simple and safe procedure, it can reduce the incidence of necrotizing enterocolitis and mortality in premature neonates less than 1500g.